The use of vaginal lubricants and ultrasound gels can have deleterious effects on sperm function - Maria Jose Soriano; Inmaculada Molina Botella; Sara Sadeghi; Andrea Palomar Rios; Sebastia Balasch; Saturnino Lujan; Nuria Pellicer; Jose Maria Rubio (Wolters Kluwer Medknow Publications, 2021)
Context: Some vaginal lubricants and ultrasound gels are known to be detrimental to sperm function and therefore could negatively affect fertility. Aims: The aim of the current study was to develop a sperm motility index (SMI) to test the sperm toxicity of ultrasound gels and vaginal lubricants used in reproductive medicine. Settings and Design: Two ultrasound gels (Aquasonic® and Kefus®) and five vaginal lubricants (Vaginesil™, Velastisa®, K-Y Jelly®, Control®, and Durex®) were studied. Three different concentrations (1%, 5%, and 10%) of each lubricant were tested. Subjects and Methods: SMI was calculated dividing the percentage of progressively motile sperm in each tested gel by that in the control at 0.5, 1, 2, and 24 h of incubation at 5% of CO2 and 37°C. SMI values <0.75 indicate sperm toxicity. Statistical Analysis Used: The main outcome measured was SMI for each concentration and time of incubation. Results: Only Durex® did not show any deleterious effect on sperm quality. The rest of lubricants presented different degrees of toxicity. Vaginesil™ resulted in toxic for all concentrations and incubation periods (SMI < 0.12). Control® and Velastisa® presented toxicity at 10% after 2 h, while K-Y Jelly® showed toxicity at 10% from 1 h of incubation. Regarding ultrasound gels, Aquasonic® showed toxic effects after only 0.5 h (SMI = 0.70 ± 0.15), while Kefus® showed slightly toxic effects after 2 h (SMI 0.69 ± 0.07). Conclusions: SMI is an accurate tool to evaluate sperm toxicity. One of the main strengths of the article is the inclusion of representative semen samples and known products used worldwide. This study has a relevant clinical translation since it highlights the importance of evaluating the possible sperm toxicity of simple products used in reproductive medicine.